2016
DOI: 10.1186/s12885-016-2648-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of night-time compression for breast cancer related lymphedema (LYNC): protocol for a multi-centre, randomized controlled efficacy trial

Abstract: BackgroundLymphedema is a prevalent long-term effect of breast cancer treatment that is associated with reduced quality of life. More recent observational data suggest that the addition of night-time compression to day-time use of a compression garment results in better long-term control of arm lymphedema. The primary objectives of the randomized controlled phase of the trial are to determine the efficacy of night-time compression on arm lymphedema volume maintenance and quality of life in breast cancer surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…This treatment requires lifelong management and the effectiveness depends on patient compliance. 29,30 Most studies in LE management are flawed by the fact that in addition to compression, several other components of DLT, especially MLD 31 are used. In our study, both patient groups had the same additional training program shown to be beneficial after lymph node intervention, 31 but no other additional components of DLT.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment requires lifelong management and the effectiveness depends on patient compliance. 29,30 Most studies in LE management are flawed by the fact that in addition to compression, several other components of DLT, especially MLD 31 are used. In our study, both patient groups had the same additional training program shown to be beneficial after lymph node intervention, 31 but no other additional components of DLT.…”
Section: Discussionmentioning
confidence: 99%
“…based instrument, was used to assess quality of life as a primary outcome in their examination of the efficacy of night-time compression on arm lymphedema volume maintenance in breast cancer survivors. 27 One challenge researchers face when reporting a study is deciding which ICF-based patient characteristics to include and report in rehabilitation studies. To facilitate this decision, researchers in rehabilitation can rely on established ICF sets, such as the ICF Generic-7 and -30 Sets and ICF Core Sets.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…11 The ICF not only makes the reporting of both clinical and population health data in an internationally comparative manner possible, the ICF as the operationalization of functioning also allows for the differentiation between a person's intrinsic biological health capacity and lived health. 4,5,12 Most importantly the ICF enables data sharing across a wide range of application areas in research, including clinical trials, [13][14][15][16] registries and cohort studies, 17,18 and in developing data collection instruments and methodologies. [18][19][20] Despite the universal understanding that functioning information, operationalized through the ICF, is the "core concept underpinning" research in rehabilitation 3 , no concrete recommendations on how to use the ICF in rehabilitation research exist to date.…”
Section: Robust Health Information Reference Systemmentioning
confidence: 99%
“…mobility, pain). 15 ICF sets have also been shown to be useful in defining functioning outcomes beyond rehabilitation studies. For example, in a multicentre cross-sectional study a questionnaire containing categories of the ICF-CS for head and neck cancer was used as one of the outcome instruments to compare functional outcome in patients with advanced head and neck cancer treated with a) surgical resection and reconstruction with microvascular free flaps followed by radiochemotherapy versus b) primary radiochemotherapy.…”
Section: Defining Functioning Categories To Be Included In Rehabilitation Studiesmentioning
confidence: 99%